Survival and reproduction of some blue-green and green algae as affected by sewage water, fertilizer factory effluent, brassica oil, phenol, toluene and benzene - Agrawal, S C; Gupta, S (Folia microbiologica, 2009)
Fourteen blue-green and green algae survived for widely different time periods ranging between 22-102 d in control culture medium. Irrespective of their long or short survival period in control cultures, their pro- or eukaryotic nature, their different morphological types or natural habitats, they all survived for a short time period ranging between 3-8 d in sewage water, 5-10 d in fertilizer factory effluent, (1/4)-2 d in brassica oil, (1/2)-2 d in phenol, 1-3 d in toluene, and 1-4 d in benzene (showing the relative toxicity of different chemicals to different algae, and the antialgal nature of brassica oil). Dilution decreased the toxicity of these agents very little, indicating that they all were very toxic to algae. None of the agent induced the formation of any reproductive or dormant cells. Sewage water, fertilizer factory effluent, brassica oil and/or benzene favored the formation of necridia cells in Phormidium bohneri, P. foveolarum, Microcoleus chthonoplastes, Lyngbya birgei, and L. major filaments. Scenedesmus quadricauda shed off all spines earlier, Hormidium flaccidum fragmented less or not at all, Scytonema millei formed no false branch and heterocyst, Aphanothece pallida and Gloeocapsa atrata cells did not divide, Cosmarium granatum cells did not form any zygospore and Oedogonium sp. not any oogonia-like cells under all or most of treatments with 25-100 % sewage water, 1-100 % fertilizer factory effluent, 1-100 % brassica oil, 25-100 % phenol, toluene and benzene.
Keywords: Reproduction; odpadní vody; toluen; Sewage; Organic Chemicals; benzen; fenol; chemické látky znečišťující vodu; Spores; spory; Water Pollutants, Chemical; Benzene; Phenol; průmyslový odpad; rozmnožování; Industrial Waste; organické látky; Toluene; Chlorophyta